Alternative Food Networks Development and Multiple Actors’ Participation in China: A Review - Huan Yang (International Journal of Agriculture System, 2016)
This article reviews the studies about the alternative food network development in China, summarizes the results and identifies the issues for further research. It first introduces different theoretical perspectives in alternative food network studies in China, including community supported agriculture, nested market, short food supply chains and producerconsumer connection. The causes of rising alternative food networks are the serious food safety problem, the un-balanced power between different actors in the mainstream agrofood system and the increasing number of middle income citizens. Its development close relates to the changes in the international agro-food system. And the government dominates the establishment of the certification system and give limited support to the emerging food networks. The consumers and majority of producers are social elites, and the small scale farmers participate in the networks under the support of intermediaries. Further studies can pay more attention to following issues: the landscape of alternative food networks development in China, the value construction processes between different actors, the role of companies in alternative food network construction and introducing technical perspective of ecological agriculture into research.